2017
DOI: 10.1016/j.jip.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal viral exposure and growth on drought stressed host plants changes resource allocation patterns and life history costs in the Speckled Wood butterfly, Pararge aegeria

Abstract: This study investigated the interactive effects of growth on drought stressed host plants and pathogen challenge with the baculovirus Autographa californica nucleopolyhedrovirus (AcMNPV) on survival and fitness-related traits using the Speckled Wood butterfly, Pararge aegeria (L.). Exposure to AcMNPV significantly reduced survival to pupation. For surviving larvae, sub-lethal infection significantly decreased daily mass acquisition rates and pupal mass. Growth on drought stressed plants increased daily mass ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 75 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…Previous studies have shown that negative effects of infection are often weaker in older or larger animals (e.g. Grove and Hoover, 2007 , Gupta et al, 2007 , Gibbs et al, 2010 , Tseng and Myers, 2014 , Gibbs and Weir, 2017 ). Here we show that even though all larvae were inoculated the same number of days after the diapause was broken, those larvae that had heavier body masses at the time of inoculation with AcMNPV developed faster during the larval stage, had longer pupal stages and higher survival to pupation.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have shown that negative effects of infection are often weaker in older or larger animals (e.g. Grove and Hoover, 2007 , Gupta et al, 2007 , Gibbs et al, 2010 , Tseng and Myers, 2014 , Gibbs and Weir, 2017 ). Here we show that even though all larvae were inoculated the same number of days after the diapause was broken, those larvae that had heavier body masses at the time of inoculation with AcMNPV developed faster during the larval stage, had longer pupal stages and higher survival to pupation.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, however, low concentration of viral exposure had no detectable effects on larval developmental time or pupal mass in the second experiment, even though it still induced increased mortality. In general, studies of the effects of baculovirus infections on larval developmental time show inconsistencies with either no, little or significant effects when infecting early instars ( Milks et al, 1998 , Matthews et al, 2002 , Monobrullah and Shankar, 2008 , Gibbs and Weir, 2017 ). In this study, larvae also reached heavier pupal mass when developing for a longer time, especially after being exposed to AcMNPV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations